Statistical estimation of linear economic relationships : distributed lags and simultaneous equations - Gupta, Y. P.; Nagar, A.L. (Rotterdam : Rotterdam University Press, 1971)
This book provides a good treatment of estimation techniques used in distributed lag models and gives a new method of estimation.
Revised version of the author's thesis, Delhi University.
Includes index.
Includes bibliographical references: p. 112-114.
ne 01/03/2018
Loans
Keywords: Economics; Estimation theory